Vikanje in tikanje v slovenskih prevodih Albeejeve drame Kdo se boji Virginie Woolf? - Onič, Tomaž (Primerjalna književnost, 2013)
Unlike Slovene, modern English does not distinguish between T-form and V-form address. The translator into Slovene must therefore introduce this distinction into the target text without clear information from the source about the level of formality or politeness expressed by this phenomenon in Slovene. The paper discusses this stylistic issue and illustrates it with a comprehensive analysis of T/V-form use in two Slovene translations of E. Albee's Who's Afraid of Virginia Woolf?
Keywords: Albee, Edward, 1928-; "Kdo se boji Virginije Woolf"; ameriška dramatika; prevodi v slovenščino; dramski slog; vikanje; tikanje; naslavljanje